ELLIPTIC FUNCTION SOLUTIONS FOR SOME NONLINEAR PDES IN MATHEMATICAL PHYSICS - Gurefe, Yusuf; Pandir, Yusuf; Akturk, Tolga; Bulut, Hasan (Wilmington Scientific Publisher, Llc, 2017)
In this work, we have constructed various types of soliton solutions of the generalized regularized long wave and generalized nonlinear Klein Gordon equations by the using of the extended trial equation method. Some of the obtained exact traveling wave solutions to these nonlinear problems are the rational function, 1-soliton, singular, the elliptic integral functions F, E, Pi and the Jacobi elliptic function sn solutions. Also, all of the solutions are compared with the exact solutions in literature, and it is seen that some of the solutions computed in this paper are new wave solutions.
Keywords: Extended trial equation method; generalized regularized long wave; generalized Klein-Gordon equation; soliton solutions; elliptic solutions